1887 Ariz. Sess. Laws 726 - (:unkn) unknown (My University, 1887)
Prohibited any person in any city, village, or town from having or carrying concealed any dirk, dirk-knife, Bowie-knife, slung-shot, brass knuckles, pistol, or other weapon. Violators fined not more than three hundred dollars, or imprisoned not more than six months, or both.
Keywords: CARRY - CONCEALED